Pengaruh Disiplin Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan PT Daya Tehnik Di Ciputat Tangerang Selatan - Alifia Galuh Pramudita; Edy Krisyanto (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract - The purpose of this study is to examine the effect of Discipline and the Physical Work Environment on Employee Performance at PT Daya Tehnik Ciputat, South Tangerang, either partially and simultaneously. This study employs an associative research method with a quantitative approach. The sampling technique used is saturated sampling, involving a total of 50 respondents. The results indicate that Discipline has a significant effect on Employee Performance, as evidenced by the regression equation (Y=5.450+0.893X1). The correlation coefficient is 0.844, indicating a very strong relationship between the two variables, with a coefficient of determination of 71.3%. The hypothesis testing (t-test) shows that the calculated tcount > ttable or (10.917 > 2.011). Therefore, H₀ is rejected and H₁ is accepted, indicating that Discipline has a significant partial effect on Employee Performance. The Physical Work Environment also has a significant effect on Employee Performance, as shown by the regression equation (Y=12.369+ 0.760X2). The correlation coefficient is 0.739, indicating a strong relationship between the variables, with a coefficient of determination of 54.6%. The t-test results indicate that the calculated tcount > ttable or (7.598 > 2.011). Thus, H₀ is rejected and H₂ is accepted, meaning that the Physical Work Environment has a significant partial effect on Employee Performance.Simultaneously, Discipline and the Physical Work Environment have a significant effect on Employee Performance, as reflected in the regression equation (Y=3.983+0.726X1+0.208X2). The correlation coefficient of 0.854 indicates a very strong relationship, with a coefficient of determination of 72.9%, while the remaining 27.1% is influenced by other factors outside this study. The F-test results show that the calculated fcount > ftable or (63.138 > 3.200). Therefore, H₀ is rejected and H₃ is accepted, indicating that Discipline and the Physical Work Environment simultaneously have a significant effect on Employee Performance at PT Daya Tehnik Ciputat, South Tangerang.